The Effect Of Product Quality And Location On Purchasing Decisions In Sakara Coffee Consumers - Wati, Novita Anjar; Alam, Iskandar Ali (LPPPIPublishing, 2024)
This research aims to find out whether product quality and location simultaneously effect purchasing decisions. In this research, quantitative methods are used. The population used was all Sakara Coffee consumers using a purposive sampling formula of 100 respondents. This research uses multiple linear regression analysis as a data analysis method. The software used to process the data is SPSS. The results of this research show that the multiple linear regression analysis is Y = 12.013 + 0.514 X1 + 0.198 X2 with a total percentage of product quality answers of 63% with an average of 82% in the Good criteria. Then 67% of the 100 samples said the location was Good with an average of 78% with Good criteria. This means that if product quality and location increase, purchasing decisions will also increase. So that the development of product quality and location will be able to attract consumer purchasing decisions and become more widely known among the public.